Energy literacy: What is out there to know? - Ana Isabel Martins; Mara Madaleno; Marta Ferreira Dias (Energy Reports, 2020)
Viewed as an essential tool, which sensitizes citizens to create sustainable energy consumption habits, energy literacy has attained a growing interest among researchers and policy makers in recent years. Energy literacy encompasses not only the cognitive domain, but also the affective and behavioral characteristics, enabling citizens to make appropriate decisions regarding energy. Considering its relevance, several studies have been carried out on this topic. In this paper, we seek to gather the main contributions of the existing literature on the subject, in order to concentrate and organize them. Most of the existent research seeks to assess the levels of literacy of the population, in the three dimensions - knowledge, affectivity and behavior -, to perceive the relationships between them, and which factors influence literacy levels. Recently another concept has emerged that relates energy literacy to financial literacy. Conciliating these two views, we present a proposal for a more comprehensive assessment of energy literacy levels, which includes the evaluation of financial and energy knowledge, without neglecting the evaluation of attitudes and behavior. This study will provide useful pointers to researchers and policy makers.
Keywords: 330; Attitude; Behavior; Decision making; Energy literacy; Knowledge